Simplified Algorithm Model for Explosion Shockwave Load in the Cabin - Qing-hua Chen; Yue-qiu Jiang; Yu-xin Gao; Yu-hang Liu; Jia-qi Yang (Shock and Vibration)
In order to obtain the shockwave load simplified algorithm model for the semiarmored projectile internal explosion in the cabin, this research made use of AUTODYN to provide a numerical modeling method for explosion in the cabin and verified the accuracy of the method via the experiment. Internal explosion simulation calculation was conducted on the operating condition numerical model with different cabin structural dimensions and different explosive loads. The cabin internal explosion space was divided into the noncorner central area, near-wall area, two-sided corner area, and three-sided corner area. Through regression of the abovementioned calculation results, an engineering model to calculate the shockwave load was obtained. It is hoped that the model can offer some references to the antiexplosion design for the ship cabin and for damage assessment of the internal explosion.